Ocean-continent subduction cannot be initiated without preceding intra-oceanic subduction! - Koptev, Alexander; Cloetingh, Sierd; Gerya, Taras; Sternai, Pietro; Botsyun, Svetlana (Frontiers in Earth Science, 2022)
The formation of new subduction zones is a key element of plate tectonics and the Wilson cycle, and many different controlling mechanisms have been proposed to initiate subduction. Here, we provide a brief overview of the known scenarios of subduction initiation in intra-oceanic and ocean-continent tectonic settings. Intra-oceanic subduction is most commonly associated with mechanical heterogeneities within the oceanic lithosphere, such as pre-existing fracture zones, spreading ridges, and transform faults. Numerous and well-recognized examples of new active subduction zones formed in intra-oceanic environments during the Cenozoic, suggesting that the initiation of ocean-ocean subduction must be a routine process that occurs “easily and frequently” in the mode of plate tectonics currently operating on Earth. On the contrary, the most traditional mechanisms for the establishment of classic self-sustaining ocean-continent subduction—passive margin collapse and subduction transference—are surprisingly rare in observations and difficult to reproduce in numerical models. Two alternative scenarios—polarity reversal and lateral propagation-induced subduction initiation—are in contrast much better documented in nature and experimentally. However, switching of subduction polarity due to arc-continent collision and lateral transmission of subducting plate boundaries are both inextricably linked to pre-existing intra-oceanic convergence. We, therefore, conclude that the onset of classic ocean-continent subduction zones is possible only through the transition from a former intra-oceanic subduction system. This transition is likely facilitated by the ductile damage accumulation and stress concentration across the aging continental margin. From this perspective, the future closure of the Atlantic Ocean can be viewed as an archetypal example of the role of transitional process between intra-oceanic subduction (Lesser Antilles) and the development of a new subduction zone at a passive continental margin (eastern North America).